ES KRIM LABU KUNING DAN PISANG KEPOK SEBAGAI ALTERNATIF JAJANAN SEHAT UNTUK ANAK SD - Winara, Zahra; Fitria, Mona; Sulaeman, Agus; Gumilar, Mulus (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2023)
As a fiber, vitamin, and minerals source, the body needs vegetable and fruit consumption for optimal growth and development. Adding pumpkin and kepok banana to ice cream is a food product development intended to increase product quality as an alternative to high β-carotene and nutritious fiber snacks. The level of β-carotene and fiber in pumpkin and kepok banana are quite high, with 1569 mcg beta-carotene and 2.7 g fiber per 100 g of pumpkin and 2.4 mcg β-carotene and 5.7 g fiber per 100 g of kepok banana. This study aims to assess the effect of pumpkin and kepok banana formulations on organoleptic properties, β-carotene levels, and fiber content of the ice cream. This research is an experimental study employing a completely randomized design (CRD) with one factor, namely the formulation of pumpkin and kepok banana at a ratio of 65%:35%, 50%:50%, and 35%:65%. Observations on the quality of ice cream comprised organoleptic testing with hedonic tests by 30 panelists with modest training, analysis of β-carotene content using HPLC method, and analysis of dietary fiber content using enzymatic gravimetric method. Using the Kruskal-Wallis test, organoleptic test data were analyzed statistically. The pumpkin and kepok banana formulation had a significant effect on the flavor and overall quality of the ice cream (p<0.05). Pumpkin and kepok banana ice cream in a ratio of 35%:65%. One serving (50 ml) of pumpkin and kepok banana ice cream provides 30.59% of β-carotene and 10.52% of their daily fiber requirements. Key words: Pumpkin, Kepok Banana, Ice Cream, Snacks, β-carotene, Fiber.